International Distribution Model for Malangan Traditional Mask SMEs: a Glocalization Strategic - Hanif Rani Iswari; Imam Mukhlis; Fulgentius Danardana Murwani (Trescode Green Organization, 2024)
This study investigates the international distribution model for SMEs producing Malangan traditional masks, with a focus on glocalization strategies. The purpose is to identify effective methods for these SMEs to penetrate global markets while preserving local cultural integrity. Employing a qualitative approach, the research gathers data through interviews with SME owners and industry experts, as well as an analysis of existing distribution channels. The findings reveal that a combination of digital marketing, strategic partnerships, and cultural adaptation is critical for successful international distribution. This model not only enhances market reach but also ensures the preservation of cultural heritage. The study provides valuable insights for SMEs in the traditional crafts sector seeking to expand globally, balancing global market demands with local cultural significance.